The Correlation Between Obesity and the Self-Image of Teenage Girls in Denpasar - Ni Made Setyaningsih; Made Rismawan; Ni Made Sri Rahyanti (Nursing and Health Sciences Journal (NHSJ), 2023)
In adolescence, the teenage girl begins to pay attention to physical appearance and wants to be close to their ideal concept of beauty, such as a slim body. The inability to appear according to the ideal concept of beauty in teenage girls with obesity causes self-image disorders. This study aims to determine the correlation between obesity and adolescent girls' self-image in Denpasar city. This study employed a correlation analysis with a cross-sectional approach. The sample in this study was 369 respondents. The sampling technique used was cluster sampling and simple random sampling. The data collection tool used was a self-image and percentile IMT questionnaire. Data analysis using chi-square test. Findings indicated that most teenage girls were not obese (72.1%), and most teenage girls had a positive self-image (96.2%). The statistical test shows p<0,001, which means a significant correlation exists between obesity and teenage girls' self-image. A study revealed a significant link between obesity and self-image among adolescent girls, with obese girls experiencing negative self-perception. The study suggests that encouraging these young women to engage in activities they excel in, like exercise and singing, could help them discover their strengths and mitigate the psychosocial effects associated with body image. Additional intervention measures are necessary to explore and reduce the broader psychosocial impact beyond body perception.